An examination of ticket pricing in a multidisciplinary sports mega-event - Francesc Solanellas; Joshua Mu\~noz; Josep Petchamé (Economies, 2022)
Some studies have examined ticket sales in the context of a sporting event. However, only a few have investigated the determinants of ticket prices, and, to date, none have done so in the context of a multidisciplinary sports mega-event. This study examines this complex paradigm through the case of the World Swimming Championships held in Barcelona, Spain. The particular focus of this study was whether, in such a framework, the same model of analysis of price determinants could be applied equally to all the disciplines that comprise the sporting mega-event. The applied model was significant, explaining the ranges of variation of the ticket prices in the different sport disciplines. The main hypothesis was rejected, which suggests that when examining price determinants in multidisciplinary sport mega-events, it will be convenient to implement a different model for each sporting discipline (aquatic, in the case at hand). These results can help professionals better understand consumer fluctuations throughout the ticket sales process in such an environment, in order to appropriately price tickets. This, in turn, will lead to maximizing revenue, as well as attendance, at sporting events.
Keywords: 330; consumer fluctuations; dynamic ticket pricing; revenues maximisation; sales management